Development of e-commerce application - Gan, Kok Kien (Nanyang Technological University, 2023)
The rise of mobile devices has dramatically impacted the way people shop and interact with businesses. E-commerce mobile applications have become increasingly popular as they provide users the convenience of shopping from anywhere at any time. Developing mobile e-commerce applications involves a complex and multifaceted process that requires careful planning, design, development and testing. These abstract overviews the key considerations and best practices for developing mobile e-commerce applications. It highlights the importance of user experience, performance, security and scalability in creating successful e-commerce applications. It also discusses the stages of e-commerce mobile application development, from initial planning and creativity to design and development and the importance of ongoing maintenance and updates. Lastly, it explores the various tools and technologies developers can use to create engaging and practical e-commerce mobile applications, including application development frameworks, cloud services and analytics tools.